TINJAUAN YURIDIS PENERAPAN UNDANG-UNDANG NO.11 TAHUN 2012 TENTANG SISTEM PERADILAN ANAK, TERHADAP SANKSI PIDANA ANAK SEBAGAI PELAKU TINDAK PIDANA NARKOTIKA (STUDI KASUS PADA WILAYAH HUKUM PENGADILAN NEGERI LUBUK PAKAM No. 10/PID/SUS-Anak/2017/PN-LBP ) - ERNAWATI BR BARUS (jurnal.unprimdn.ac.id, 2021)
The child is a treasure God Almighty that is highly anticipated by a family, because aside from being a descendant of a family of children as well as the next generation of the nation and successor development, namely a generation that is prepared as a subject of implementing sustainable development and control the future of a country. As time goes by children not only as a victim in a crime but there have been many children involved as perpetrators of the crime, in this case was the crime of narcotics is one of the extraordinary crime or